Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.aju.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of male infertility by the World Health Organization laboratory manual for assessment of semen analysis: A systematic review

Abstract: ObjectiveTo discuss the role, reliability and limitations of the semen analysis in the evaluation of fertility with reference to the World Health Organization (WHO) fifth edition guidelines, with semen analysis reference values published in 2010. We also discuss the limitations of using a single threshold value to distinguish ‘abnormal’ and ‘normal’ parameters.MethodsThe Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used to search the MEDLINE, EMBASE, and the Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 38 publications
(63 reference statements)
1
55
0
2
Order By: Relevance
“…According to the WHO criteria established in 2010, presented in Table 1, the seminal parameters values must fall within standard reference range, although some authors discuss in their papers about the drawbacks of using a single threshold value to distinguish the normal and abnormal values of seminal parameters (Patel et al 2018, [8]).…”
Section: Methodsmentioning
confidence: 99%
“…According to the WHO criteria established in 2010, presented in Table 1, the seminal parameters values must fall within standard reference range, although some authors discuss in their papers about the drawbacks of using a single threshold value to distinguish the normal and abnormal values of seminal parameters (Patel et al 2018, [8]).…”
Section: Methodsmentioning
confidence: 99%
“…As a result, there is significant intra-individual variability of seminal parameters, which, in one study was found between 10.3% and 26.8% (Alvarez et al, 2003). Therefore, semen analysis has its limitations in predicting the fertility potential of a man, except in cases of severe abnormalities (Patel et al, 2018). Despite these limitations, the semen analysis is an indispensable part of initial evaluation of the male partner (Esteves, 2014).…”
Section: Articlementioning
confidence: 99%
“…Unlike the previous versions of the WHO editions, the fifth edition (2010) was based on a precisely defined population, from 1953 semen samples, collected from recent fathers with TTP (Time to pregnancy) up to and including 12 months (Cooper et al, 2010). This edition was unique because it defined the reference values in terms of percentile (Cooper et al, 2010;WHO, 2010;Patel et al, 2018). Penn et al (2011) speculated that in future, such percentile range, rather than the absolute value, might be used to determine the need of intervention.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…The last (fifth) edition of the manual, published in 2010, defines serious decrease in cutoff values for sperm parameters related to chances of achieving pregnancy and thus its significance was widely discussed [3,4]. One of the strong limitations of semen analysis and the defined fertility potential references in the last WHO edition is the lack of correlation with the female age, as only 30% of infertility in couples is due to male factors alone [5,6]. The sixth edition of WHO is in discussion as some of the directions of changes would be: semen analysis references including the Asian population for reference establishment; additional separate chapters for sperm morphology and computer assisted sperm analysis (CASA); importance of microbiological assessment.…”
Section: Introductionmentioning
confidence: 99%